(untitled) (World Economics and Finance Bulletin, 2022)
The author of the article analyzes the impact of the formation of the digital economy on labour relations and social security relations from the point of view of the impact of digitization on employment. The article concludes that this process has both positive (possibility to combine work and family obligations, development of remote work) and negative (reduction in number/number of employees, problems of employing the elderly) sides. The digitalization of the economy occurs as a result of scientific and technological progress and the fourth industrial revolution, influencing business processes and markets. An analysis of the labour market showed a decrease in the unemployment rate, which is currently within its natural norm. The ratio of the growth in the number of unemployed and employed to GDP growth rates reflects the weak reaction of the labour market to shocks in the economic environment. Employment is inelastic. It has been established that new technologies contribute not so much to the transformation of the employment structure as to the content of the operations performed and the functionality of professions.